2016
DOI: 10.3746/pnf.2016.21.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Juice Administration Decreases Liver Stearoyl-CoA Desaturase 1 and Improves Docosahexaenoic Acid Levels, but Not Steatosis in High Fructose Diet-Fed Weanling Wistar Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent liver diseases associated with an altered lifestyle, besides genetic factors. The control and management of NAFLD mostly depend on lifestyle modifications, due to the lack of a specific therapeutic approach. In this context, we assessed the effect of carrot juice on the development of high fructose-induced hepatic steatosis. For this purpose, male weanling Wistar rats were divided into 4 groups, fed either a control (Con) or high fructose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…The current study showed that the high-fructose diet did not change the liver and body weights, but significantly elevated hepatic TG, plasma TG, and plasma TC levels. Similar to our observation, in a study by Mahesh et al [ 29 ], a high-fructose diet induced fatty liver without significant differences in body or liver weight for 8 weeks. Similarly, Kawasaki et al [ 7 ] reported that, in a study of rats fed a high-fructose, high-fat, or high-sucrose diet for 6 weeks, there was no significant difference in the body weight or liver weight in the high-fructose or high-sucrose-diet groups compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed that the high-fructose diet did not change the liver and body weights, but significantly elevated hepatic TG, plasma TG, and plasma TC levels. Similar to our observation, in a study by Mahesh et al [ 29 ], a high-fructose diet induced fatty liver without significant differences in body or liver weight for 8 weeks. Similarly, Kawasaki et al [ 7 ] reported that, in a study of rats fed a high-fructose, high-fat, or high-sucrose diet for 6 weeks, there was no significant difference in the body weight or liver weight in the high-fructose or high-sucrose-diet groups compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…However, despite a significant increase in plasma FFA levels, which is known to be associated with the development of insulin resistance, high fructose diet‐fed animals did not display hyperinsulinemia and impaired glucose tolerance. In addition, although resistin and IGFBP levels increased in RPWAT owing to carrot juice feeding, it had no effect on insulin sensitivity, which is evident from the unaltered glucose uptake of skeletal muscle in these animals …”
Section: Discussionmentioning
confidence: 82%
“…Soleus muscles were excised immediately after the animals were sacrificed and processed for glucose uptake assay according to the previously described method [ 18 ].…”
Section: Methodsmentioning
confidence: 99%